2019
DOI: 10.1002/ijc.32134
|View full text |Cite|
|
Sign up to set email alerts
|

NUF2 is a valuable prognostic biomarker to predict early recurrence of hepatocellular carcinoma after surgical resection

Abstract: Early tumor recurrence after curative surgical resection poses a great challenge to the clinical management of hepatocellular carcinoma (HCC). We conducted whole genome expression microarrays on 64 primary HCC tumors with clinically defined recurrence status and cross‐referenced with RNA‐seq data from 18 HCC tumors in the Cancer Genome Atlas project. We identified a 77‐gene signature, which is significantly associated with early recurrent (ER) HCC tumors. This ER‐associated signature shows significant enrichme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…NUF2 is a component of a protein complex associated with the centromere that plays an important role in chromosome segregation [29]. Previous studies have shown that NUF2 is an effective prognostic molecule for hepatocellular carcinoma [30], and silencing NUF2 can suppress human hepatocellular carcinoma tumor growth and induce apoptosis [31]. In addition, NUF2 overexpression is also related to poor prognosis in pancreatic cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…NUF2 is a component of a protein complex associated with the centromere that plays an important role in chromosome segregation [29]. Previous studies have shown that NUF2 is an effective prognostic molecule for hepatocellular carcinoma [30], and silencing NUF2 can suppress human hepatocellular carcinoma tumor growth and induce apoptosis [31]. In addition, NUF2 overexpression is also related to poor prognosis in pancreatic cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, NUF2, one of a potential prognostic marker detected in our analysis, was reported to be a prognostic biomarker for early HCC recurrence in another HCC cohort. 56 In addition, ASPM, another potential prognostic marker reported in our analysis, which mRNA levels was overexpressed in HCC tissues and was found as a marker predicting enhanced invasive potential and poor prognosis of HCC by Lin et al 57 The correlation between mRNA and protein expression is a matter of scientific issue, and studies have revealed that the process of mRNA translation to protein is complicated. 20 Of note, the expression of some CT proteins might be regulated posttranscriptionally; thus, the expression of CT gene mRNA may not guarantee protein expression, which therefore limits its generalization as candidate therapeutic targets.…”
Section: Discussionmentioning
confidence: 59%
“…NUF2 is a composition of a molecular linker between the kinetochore attachment site and the tubulin subunits within the lattice of the attached plus ends [19]. NUF2 is also an oncogene that is over-expressed on several cancers [5,20], including lung adenocarcinoma. Comparing with previous study, the NUF2 expression in multiple databases was signi cantly higher than in normal tissues, and also signi cantly higher in LUAD and LUSC [7].…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear division cycle 80(NDC80) complex is a heterotetrameric protein complex, and NUF2, as an important part of the NDC80 complex, is essential for kinetochore-microtubule attachment and chromosome separation [3]. Previous evidence demonstrated that NUF2 plays as a prognostic biomarker and therapeutic target in hepatocellular carcinoma, breast cancer and oral cancer [4][5][6], and NDC80 complex gene might be an early indicator of diagnosis and prognosis of lung adenocarcinoma [7]. These studies have shown that NUF2 might be a candidate biomarker and therapeutic target in cancer with great potential, but the role of the NUF2 gene in NSCLC has not been systematically explored in multiple aspects.…”
Section: Introductionmentioning
confidence: 99%